Multi-principal-phase Ce-rich sintered magnet and preparation method thereof
By adding sintered Nd-Fe-B sludge to Ce-rich main phase alloy magnetic powder, and building a Pr\Nd-rich shell using in-situ diffusion technology, the high preparation of multi-main phase rich Ce sintered magnets in the prior art is solved. The problem of unbalanced utilization of cost and rare earth resources has achieved the preparation of low-cost, high-magnetic performance, multi-main phase rich Ce sintered magnets.
Patent Information
- Application Number
- CN202411671369.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
In the preparation of multi-main phase Ce-rich sintered magnets, the prior art relies on Nd-rich fastening sheets and high-cost calcium reduction processes, resulting in high production costs and unbalanced utilization of rare earth resources.
Purification of magnetic powder by adding sintered Nd-Fe-B sludge to Ce-rich main phase alloy magnetic powder, the Pr\Nd2Fe14B main phase grains with high magnetic crystal anisotropy field are used to provide the Pr\Nd2Fe14B main phase grains with high magnetic crystal anisotropy field and diffuse in situ Technology constructs a Pr\Nd-rich shell to prepare multi-main phase Ce-rich sintered magnets.
The multi-main phase rich Ce sintered magnet with better magnetic properties is achieved at low cost, which promotes the balanced utilization of rare earth resources and the high-value reuse of sintered Nd-Fe-B sludge.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth magnetic material preparation, and in particular to a multi-main-phase Ce-rich sintered magnet and a preparation method thereof. Background Art
[0002] Rare earth permanent magnet materials are the largest application field of rare earth resources. They are also the key basic materials supporting the leapfrog development of strategic emerging industries and future industries such as new energy vehicles, advanced rail transportation equipment, high-end CNC machine tools and robots. In recent years, the rare earth permanent magnet industry has developed rapidly, the output of sintered Nd-Fe-B magnets has increased year by year, and the demand for rare earths such as Nd, Pr, Dy, and Tb has also increased sharply. Due to the coexistence of rare earth elements in rare earth ores, excessive consumption of Nd, Pr, Dy, and Tb elements for the manufacture of Nd-Fe-B permanent magnets accounts for about 70wt.% of the total rare earth reserves. Cheap light rare earth elements such as La and Ce have been largely shelved due to limited market demand, resulting in an unbalanced utilization of rare earth resources in my country. In addition, a large amount of oily sludge waste will be generated during the mechanical processing of sintered Nd-Fe-B magnets. The increase in the annual output of sintered Nd-Fe-B magnets has also led to an increase in the amount of oily sludge waste generated during the mechanical processing process. These oily sludges are mainly composed of RE2Fe 14 B phase is a valuable secondary resource of rare earth permanent magnets. Therefore, using high-abundance, low-cost Ce and sintered Nd-Fe-B sludge to prepare multi-phase Ce-rich sintered magnets is an important way to promote the efficient application of rare earth resources in my country, and has very important strategic significance in terms of economic benefits and sustainable development.
[0003] In terms of Ce element utilization, due to Ce2Fe 14 The intrinsic performance of B is much lower than that of Nd2Fe 14 B and Pr2Fe 14 B, Ce replacing Nd and Pr will reduce RE2Fe 14The intrinsic magnetic properties of the tetragonal phase B lead to a strong magnetic dilution effect. In order to weaken the magnetic dilution effect caused by the introduction of Ce elements, a dual-phase alloy process is currently used to design and prepare a Ce-containing main phase magnetic powder and a Ce-free main phase magnetic powder, which are uniformly mixed in a certain proportion to prepare a multi-main phase Ce-based sintered magnet. Compared with single-main phase magnets, the rare earth elements in a single main phase grain of a multi-main phase magnet are unevenly distributed and present a "core-shell" structure, as well as Ce-rich and Ce-poor grains. The chemical composition heterogeneity caused by the uneven distribution of rare earth elements inside the main phase grains and between grains can effectively weaken the magnetic dilution effect caused by the introduction of Ce. For example, the invention patents 201210315684.5 and 201310090328.2 use a dual-phase alloy process to prepare two quick-setting sheets with different compositions, and obtain the final multi-phase magnet after crushing, powdering, mixing, sintering and heat treatment. At least one quick-setting sheet used contains a Nd-rich 2:14:1 main phase, and the Nd2Fe 14 In the prior art, the dual-phase alloy process for preparing Ce magnets must use Nd-rich quick-solidified sheets and then use hydrogen crushing and air flow milling to prepare magnetic powder as Nd2Fe 14 The source of B grains is obviously not conducive to further reducing the manufacturing cost of Ce magnets and reducing the dependence on Pr and Nd rare earth elements.
[0004] In addition, in response to the increase in the amount of sintered Nd-Fe-B sludge, in addition to using traditional hydrometallurgy or pyrometallurgy to recover sintered Nd-Fe-B sludge to extract rare earth elements, in recent years, the use of purification and calcium reduction technology to directly reduce sintered Nd-Fe-B sludge into recycled magnetic powder, and then re-prepare blanks through oriented pressing, sintering and heat treatment has developed rapidly as a new green technology, as described in invention patents 201710762926.8 and 201811437315.7. However, the calcium reduction process is costly, the amount of sludge processed in a single time is low, and the recycled magnetic powder cannot be directly used to prepare magnets due to the severe loss of rare earths and high oxygen content. It is usually necessary to add a large amount of high-performance Nd-Fe-B air flow milling, rare earth hydride and rare earth-rich alloy powder to prepare recycled magnets. Unfortunately, the production cost of such recycled magnets is high and the magnetic properties are low, which cannot reflect the value of sludge as a secondary resource of rare earth permanent magnets. The recent invention patent 202311016299.5 directly adds high-performance Nd-Fe-B air flow milled powder and Pr-rich and Nd-rich rare earth alloy powder to the purified sintered Nd-Fe-B sludge to increase the overall rare earth content to prepare medium and low-grade recycling magnets. Although this method omits the calcium reduction process, it still requires the use of a large amount of non-high-abundance rare earth elements Pr, Nd, etc. other than La, Ce, and Y in the preparation of medium and low-grade magnets, which is not conducive to the balanced utilization of rare earth resources and further reduction of production costs.
[0005] In summary, on the one hand, in order to reduce the backlog of Ce elements, promote the balanced utilization of rare earth resources, and give full play to its advantages as a high-abundance rare earth resource, on the other hand, in order to utilize sintered Nd-Fe-B sludge at high value, there is an urgent need for a new method to prepare multi-main-phase Ce-rich sintered magnets by using high-abundance rare earth Ce and sintered Nd-Fe-B sludge to achieve the replacement of medium and low-grade magnets. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a multi-main phase Ce-rich sintered magnet and a preparation method thereof, wherein sintered Nd-Fe-B oil sludge is added to Ce-rich main phase alloy magnetic powder to purify the magnetic powder, and the sintered Nd-Fe-B oil sludge is used to provide a multi-main phase Ce-rich sintered magnet with a high magnetocrystalline anisotropy field (H A ) of Pr\Nd2Fe 14 B main phase grains; further control the particle size and sintering process of Ce-rich main phase alloy powder and sintered Nd-Fe-B oil sludge magnetic powder, and combine the in-situ diffusion technology to construct a high H A The Pr\Nd-rich shell layer is formed, thereby realizing the preparation of multi-main-phase Ce-rich sintered magnets with better magnetic properties by sintering Nd-Fe-B sludge.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A multi-phase Ce-rich sintered magnet, the multi-phase Ce-rich sintered magnet is composed of a main alloy A and an auxiliary alloy B in a mass ratio of 9-6:1-4, and the sum of the mass ratios of the main alloy A and the auxiliary alloy B is 10; the main alloy A is a Ce-rich main phase, and its chemical formula is [Re a Ce 1-a ] x Fe 100-x-y-z M y B z , wherein the Ce content is greater than 12.0wt.%, Re is one or more of Pr and Nd, M is one or more of Nb, Ti, V, Zr, Co, Mn, Ni, Ga, Al, Au, and Cu, and a, x, y, and z satisfy the following relationship: 0.3≤a≤0.6, 32≤x≤35, 0.5≤y≤3, 0.8≤z≤1.0; and the auxiliary alloy B is sintered Nd-Fe-B sludge.
[0009] The preparation method of multi-phase Ce-rich sintered magnet comprises the following steps:
[0010] (1) According to the chemical formula of the main alloy A, various metal components and other components are selected and placed in a crucible. After the materials are baked under vacuum, argon gas is filled in for melting, and then the materials are poured onto a rotating water-cooled copper roller to prepare a quick-setting sheet;
[0011] (2) subjecting the quick-setting flakes obtained in step (1) to hydrogen crushing treatment to obtain hydrogen crushing coarse powder A after dehydrogenation, and then adding a lubricant and an antioxidant to mix evenly to obtain a mixed coarse powder for later use;
[0012] (3) The mixed coarse powder in the above step (2) is subjected to air flow grinding to obtain fine powder A with an average particle size of 2.5-4.0 μm for standby use;
[0013] (4) using the sintered Nd-Fe-B sludge as auxiliary alloy B, and washing and purifying the sludge to obtain a coarse sludge powder for later use;
[0014] (5) adding a lubricant to the above coarse oil sludge powder and subjecting it to jet milling treatment to obtain oil sludge fine powder B with an average particle size of 1.0-2.5 μm for later use;
[0015] (6) The fine powder A and the oil sludge fine powder B are mixed in a mass ratio of 9-6:1-4 to obtain a mixed fine powder C, and a lubricant and an antioxidant are added to mix evenly, and oriented and formed in a magnetic field with a magnetic field strength of 1.5-2.5T under the protection of an inert gas, and then vacuum packaged and cold isostatically pressed to obtain a green body for use;
[0016] (7) placing the green body into a vacuum sintering furnace for sintering-diffusion coordinated treatment: first, keeping the temperature at 960-1000° C. for 5-8 hours, then cooling the temperature to 800-900° C. for 2-6 hours, and finally cooling the green body to room temperature with argon gas to obtain a multi-phase magnet;
[0017] (8) The multi-phase magnet is placed in a vacuum sintering furnace for two-stage heat treatment, wherein the first stage heat treatment temperature is 680-780°C for 2-4 hours, and the second stage heat treatment temperature is 390-490°C for 3-6 hours.
[0018] Preferably, in step (1), the rotation speed of the water-cooled copper roller is 1-3 m / s, and the thickness of the quick-setting sheet is 150-350 μm.
[0019] Preferably, in step (2), the amount of lubricant added is 0.05%-0.8% of the total mass of the hydrogen-crushed coarse powder A, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the hydrogen-crushed coarse powder A.
[0020] Preferably, the oil sludge in step (4) is oil sludge produced by grinding machine processing, and the cleaning and purification method is first stirring and cleaning with OP emulsifier ethanol solution, centrifuging and magnetic separation to remove non-magnetic substances, then stirring and cleaning with hydrochloric acid ethanol solution and nitric acid ethanol solution and magnetic separation to reduce the oxide content, and finally vacuum drying to obtain purified oil sludge coarse powder.
[0021] Preferably, the amount of lubricant added in step (5) is 0.05%-0.8% of the total mass of the purified sludge coarse powder.
[0022] Preferably, in step (6), the amount of lubricant added is 0.05%-0.8% of the total mass of the mixed fine powder C, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the mixed fine powder C.
[0023] The present invention provides a multi-phase Ce-rich sintered magnet and a preparation method thereof, which has the following advantages over the prior art:
[0024] (1) The present invention uses high-abundance rare earth element Ce and sintered Nd-Fe-B sludge to prepare multi-phase Ce-rich sintered magnets, which not only promotes the balanced utilization of rare earth resources, but also solves the problem of high-value reuse of sintered Nd-Fe-B sludge, which is of great significance in terms of economic efficiency and sustainable development;
[0025] (2) The present invention uses a dual-phase alloy process to provide a high H A Pr\Nd2Fe 14 B grains, and by designing the particle sizes of the two main phase alloy powders, the smaller particle size of Pr\Nd2Fe 14The B grains are evenly dispersed around the Ce-rich main phase grains. During the long sintering-diffusion heat treatment, the two main phase grains undergo solid-solid diffusion, forming a Pr\Nd-rich shell layer on the surface of the Ce-rich main phase grains, and maintaining a small grain size, thereby significantly improving the coercivity of the multi-main phase Ce-rich sintered magnet;
[0026] (3) The multi-phase Ce-rich sintered magnet prepared by the present invention has lower production cost than the multi-phase Ce-rich sintered magnet prepared by the traditional dual alloy process, and gives full play to the advantages of high-abundance rare earth resources and sintered Nd-Fe-B sludge. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The following lubricants are Nd-Fe-B special lubricant 6# produced by Tianjin Yuesheng New Materials Research Institute;
[0029] The antioxidant is Nd-Fe-B special antioxidant 5# produced by Tianjin Yuesheng New Materials Research Institute
[0030] Embodiment 1:
[0031] Preparation of multi-phase Ce-rich sintered magnets by sintering Nd-Fe-B sludge:
[0032] According to the nominal composition of the main alloy A (Ce 0.5 Nd 0.5 ) 34.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), using a copper roller speed of 1.3 m / s, a quick-setting sheet with a thickness of about 220 μm was prepared. Then the quick-setting sheet was hydrogen-crushed, and after dehydrogenation, a coarsely crushed magnetic powder was obtained, and then 0.06% of a lubricant and 0.08% of an antioxidant were added to the mixture, and the mixture was fully mixed and then jet milled under an inert gas atmosphere to obtain an average particle size of X 50 The jet milled powder A is 3.5 μm.
[0033] The sintered Nd-Fe-B sludge produced by grinding was selected as auxiliary alloy B. The main components detected by ICP were: Pr6.95 Nd 21.84 Fe bal Cu 0.18 Co 0.73 Ga 0.13 Zr 0.24 B 0.94 First, the oil sludge was placed in a 5wt.% OP emulsifier ethanol solution and stirred for washing for 15 minutes, and non-magnetic substances were removed by centrifugation and magnetic separation, and the above process was repeated 3 times; then the oil sludge obtained after preliminary cleaning was placed in a 1wt.% nitric acid ethanol solution and stirred for washing for 5 minutes, and the above process was repeated 3 times; and then dried in a vacuum environment to obtain a purified oil sludge coarse powder.
[0034] Add 0.08% lubricant by mass to the purified sludge coarse powder, mix thoroughly and then perform air flow milling to obtain an average particle size of X 50 The oil sludge fine powder B is 1.6 μm.
[0035] In a glove box, the jet-milled powders of components A and B were mixed in a mass ratio of 7.0:3.0, and then 0.10% of a lubricant and 0.12% of an antioxidant were added thereto and mixed evenly to obtain jet-milled powder C with a Ce content of 11.90 wt.%.
[0036] Under an inert gas protective atmosphere, the jet milled powder C is oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact is vacuum packaged and cold isostatically pressed and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. First, it is kept at 980℃ for 6 hours, then the temperature is reduced to 880℃ and kept for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment is performed at low temperature, first at 740℃ for 3 hours, then cooled to room temperature with argon gas, and then at 400℃ for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C, which is placed in a BH tester to test the magnetic properties. The results are as follows:
[0037] Magnet C: B r =12.34 kG, H cj =12.63kOe, (BH) max =36.41MGOe, H k / H cj =95.8%.
[0038] Embodiment 2:
[0039] Preparation of multi-phase Ce-rich sintered magnets by sintering Nd-Fe-B sludge:
[0040] According to the nominal composition of the main alloy A1 (Ce 0.6 Nd 0.4 ) 34.0 Fe bal Al0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), using a copper roller speed of 1.3 m / s, a quick-setting sheet with a thickness of about 220 μm was prepared. Then the quick-setting sheet was hydrogen-crushed, and after dehydrogenation, a coarsely crushed magnetic powder was obtained, and then 0.06% of a lubricant and 0.08% of an antioxidant were added to the mixture, and the mixture was fully mixed and then jet milled under an inert gas atmosphere to obtain an average particle size of X 50 The jet milled powder A1 is 3.5 μm.
[0041] The sintered Nd-Fe-B sludge produced by grinding was selected as auxiliary alloy B. The main components detected by ICP were: Pr 6.95 Nd 21.84 Fe bal Cu 0.18 Co 0.73 Ga 0.13 Zr 0.24 B 0.94 First, the oil sludge was placed in a 5wt.% OP emulsifier ethanol solution and stirred for washing for 15 minutes, and non-magnetic substances were removed by centrifugation and magnetic separation, and the above process was repeated 3 times; then the oil sludge obtained after preliminary cleaning was placed in a 1wt.% nitric acid ethanol solution and stirred for washing for 5 minutes, and the above process was repeated 3 times; and then dried in a vacuum environment to obtain a purified oil sludge coarse powder.
[0042] Add 0.08% lubricant by mass to the purified sludge coarse powder, mix thoroughly and then perform air flow milling to obtain an average particle size of X 50 The oil sludge fine powder B is 1.6 μm.
[0043] In a glove box, the jet-milled powders of components A1 and B were mixed in a mass ratio of 6.0:4.0, and then 0.10% of a lubricant and 0.12% of an antioxidant were added thereto and mixed evenly to obtain jet-milled powder C1 with a Ce content of 12.24 wt.%.
[0044] Under an inert gas protective atmosphere, the jet milled powder C1 was oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact was vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. It was first kept at 980°C for 6 hours, then lowered to 880°C for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment was performed at low temperature, first at 740°C for 3 hours, then cooled to room temperature with argon gas, and then at 400°C for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C1, which was placed in a BH tester to test the magnetic properties. The results are as follows:
[0045] Magnet C1: B r =12.49kG, H cj =12.06kOe, (BH) max =38.07MGOe, H k / H cj =96.1%.
[0046] Comparative Example 1:
[0047] The traditional dual alloy process is used to prepare multi-phase Ce-rich sintered magnets:
[0048] According to the nominal composition of the main alloy A (Ce 0.5 Nd 0.5 ) 34.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), based on the nominal composition Nd of auxiliary alloy B1 31 Fe bal Al 0.1 Cu 0.5 Co 0.8 Ga 0.35 Zr 0.2 B 0.95 (wt.%), and a copper roller speed of 1.3 m / s was used to prepare quick-setting sheets of components A and B1 with a thickness of about 220 μm.
[0049] The quick-setting flakes of components A and B1 were hydrogen-crushed to obtain coarsely crushed magnetic powder after dehydrogenation. Then, 0.06% of lubricant and 0.08% of antioxidant were added and mixed well. Then, the mixture was jet-milled under an inert gas atmosphere to obtain jet-milled fine powders of components A and B1. The average particle size of the jet-milled powder of component A was X 50 The average particle size of the jet milled powder of component B1 is 3.5 μm. 50 It is 2.6μm.
[0050] In the glove box, 0.12% of lubricant and 0.16% of antioxidant were added to the airflow milled powders of components A and B1 respectively and mixed evenly. Then, the airflow milled powders of components A and B1 were mixed in a mass ratio of 7.0:3.0 to obtain airflow milled powder C2 with a Ce content of 11.90wt.%.
[0051] Under an inert gas protective atmosphere, the jet milled powder C2 is oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact is vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for conventional sintering process. After sintering at 1040°C for 5 hours, it is cooled to room temperature with argon gas. Then, two steps of conventional heat treatment are performed, first at 820°C for 3 hours, then cooled to room temperature with argon gas, and then at 400°C for 4 hours, then cooled to room temperature with argon gas. The multi-phase magnet C2 is obtained, and the magnetic properties are tested in a BH tester. The results are as follows:
[0052] Magnet C2: B r =12.12kG, H cj =12.34kOe, (BH) max =34.76MGOe, H k / H cj =96.2%.
[0053] Comparative Example 2:
[0054] The multi-phase Ce-rich sintered magnets are prepared by using the traditional dual alloy process combined with sintering-in-situ diffusion heat treatment:
[0055] According to the nominal composition of the main alloy A (Ce 0.5 Nd 0.5 ) 34.0 Fe bal Al 0.8 Cu 0.5 Co1Ga 0.35 Zr 0.2 B 0.95 (wt.%), based on the nominal composition Nd of auxiliary alloy B1 31 Fe bal Al 0.1 Cu 0.5 Co 0.8 Ga 0.35 Zr 0.2 B 0.95 (wt.%), and a copper roller speed of 1.3 m / s was used to prepare quick-setting sheets of components A and B1 with a thickness of about 220 μm.
[0056] The quick-setting flakes of components A and B1 were hydrogen-crushed to obtain coarsely crushed magnetic powder after dehydrogenation. Then, 0.06% of lubricant and 0.08% of antioxidant were added and mixed well. Then, the mixture was jet-milled under an inert gas atmosphere to obtain jet-milled fine powders of components A and B1. The average particle size of the jet-milled powder of component A was X 50 The average particle size of the jet milled powder of component B1 is 3.5 μm. 50 It is 2.6μm.
[0057] In the glove box, 0.12% of lubricant and 0.16% of antioxidant were added to the airflow milled powders of components A and B1 respectively and mixed evenly. Then, the airflow milled powders of components A and B1 were mixed in a mass ratio of 7.0:3.0 to obtain airflow milled powder C2 with a Ce content of 11.90wt.%.
[0058] Under an inert gas protective atmosphere, the jet milled powder C2 is oriented and formed in a magnetic field with a magnetic field strength of 2.0T to obtain a green compact. The green compact is vacuum packaged and cold isostatically pressed, and then placed in a vacuum sintering furnace for sintering-diffusion process coordinated treatment. First, it is kept at 980℃ for 6 hours, then the temperature is reduced to 880℃ and kept for 4 hours, and then cooled to room temperature with argon gas; then a two-step heat treatment is performed at low temperature, first at 740℃ for 3 hours, then cooled to room temperature with argon gas, and then at 400℃ for 4 hours, then cooled to room temperature with argon gas, to obtain a multi-phase magnet C3, which is placed in a BH tester to test the magnetic properties. The results are as follows:
[0059] Magnet C3: B r =12.09kG, H cj =13.56kOe, (BH) max =35.23MGOe, H k / H cj =97.3%.
[0060] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A multi-phase Ce-rich sintered magnet, characterized in that: The multi-main-phase Ce-rich sintered magnet is composed of a main alloy A and an auxiliary alloy B in a mass ratio of 9-6:1-4, and the sum of the mass ratios of the main alloy A and the auxiliary alloy B is 10; The main alloy A is a Ce-rich main phase, and its chemical formula is [Re a Ce 1-a ] x Fe 100-x-y-z M y B z , wherein the Ce content is greater than 12.0wt.%, Re is one or more of Pr and Nd, M is one or more of Nb, Ti, V, Zr, Co, Mn, Ni, Ga, Al, Au, and Cu, and a, x, y, and z satisfy the following relationship: 0.3≤a≤0.6, 32≤x≤35, 0.5≤y≤3, and 0.8≤z≤1.0; The auxiliary alloy B is sintered Nd-Fe-B sludge.
2. A method for preparing a multi-phase Ce-rich sintered magnet as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) According to the chemical formula of the main alloy A, various metal components and other components are selected and placed in a crucible. After the materials are baked under vacuum, argon gas is filled in for melting, and then the materials are poured onto a rotating water-cooled copper roller to prepare a quick-setting sheet; (2) subjecting the quick-setting flakes obtained in step (1) to hydrogen crushing treatment to obtain hydrogen crushing coarse powder A after dehydrogenation, and then adding a lubricant and an antioxidant to mix evenly to obtain a mixed coarse powder for later use; (3) The mixed coarse powder in the above step (2) is subjected to air flow grinding to obtain fine powder A with an average particle size of 2.5-4.0 μm for standby use; (4) using the sintered Nd-Fe-B sludge as auxiliary alloy B, and washing and purifying the sludge to obtain a coarse sludge powder for later use; (5) adding a lubricant to the above coarse oil sludge powder and subjecting it to jet milling treatment to obtain oil sludge fine powder B with an average particle size of 1.0-2.5 μm for later use; (6) The fine powder A and the oil sludge fine powder B are mixed in a mass ratio of 9-6:1-4 to obtain a mixed fine powder C, and a lubricant and an antioxidant are added to mix evenly, and oriented and formed in a magnetic field with a magnetic field strength of 1.5-2.5T under the protection of an inert gas, and then vacuum packaged and cold isostatically pressed to obtain a green body for use; (7) placing the green body into a vacuum sintering furnace for sintering-diffusion coordinated treatment: first, keeping the temperature at 960-1000° C. for 5-8 hours, then cooling the temperature to 800-900° C. for 2-6 hours, and finally cooling the green body to room temperature with argon gas to obtain a multi-phase magnet; (8) The multi-phase magnet is placed in a vacuum sintering furnace for two-stage heat treatment, wherein the first stage heat treatment temperature is 680-780°C for 2-4 hours, and the second stage heat treatment temperature is 390-490°C for 3-6 hours.
3. The preparation method according to claim 2, characterized in that: In the step (1), the rotation speed of the water-cooled copper roller is 1-3 m / s, and the thickness of the quick-setting sheet is 150-350 μm.
4. The preparation method according to claim 2, characterized in that: In the step (2), the amount of lubricant added is 0.05%-0.8% of the total mass of the hydrogen-crushed coarse powder A, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the hydrogen-crushed coarse powder A.
5. The preparation method according to claim 2, characterized in that: The oil sludge in step (4) is the oil sludge produced by grinding machine processing, and the cleaning and purification method is firstly to stir and clean it with OP emulsifier ethanol solution, centrifuge and magnetic separation to remove non-magnetic substances, then to stir and clean it with hydrochloric acid ethanol solution and nitric acid ethanol solution and magnetic separation to reduce the oxide content, and finally to obtain the purified oil sludge coarse powder through vacuum drying.
6. The preparation method according to claim 2, characterized in that: The amount of lubricant added in step (5) is 0.05%-0.8% of the total mass of the purified sludge coarse powder.
7. The preparation method according to claim 2, characterized in that: In the step (6), the amount of lubricant added is 0.05%-0.8% of the total mass of the mixed fine powder C, and the amount of antioxidant added is 0.05%-1.0% of the total mass of the mixed fine powder C.
Citation Information
Patent Citations
Low-cost dual-phase Ce permanent magnet alloy and its preparation method
CN102800454B
A kind of rare earth permanent magnet alloy and its magnetic phase compound preparation method
CN103187133B
Method for preparing recycled sintered NdFeB magnets from NdFeB sludge waste processed by double-sided grinding
CN107424700B
Method for recovering neodymium iron boron trepanning oil sludge waste through Ca-chloride reduction diffusion technology
CN109338113A
Ultra-short process engineering recovery technology for sintered neodymium iron boron oil sludge
CN117066503A